Alcohol and new onset atrial fibrillation: a case-control study of a current series. Issue 5 (May 1987) - Koskinen, P; Kupari, M; Leinonen, H; Luomanmäki, K
Abstract : The aetiological role of alcohol in new onset atrial fibrillation was evaluated in a case-control study of 100 consecutive patients aged 21-64 years. Clinical examination, routine diagnostic tests, and echocardiography revealed an underlying disease or other identifiable factor for atrial fibrillation in 65 patients (group 1); 35 patients had idiopathic atrial fibrillation (group 2). The most common diseases associated with atrial fibrillation were ischaemic heart disease (21%), hypertension (13%), and cardiomyopathy (8%). Data on alcohol consumption were obtained by interviewing the patients and their age and sex matched controls on admission. The mean daily alcohol intake of group 2 patients during the week preceding atrial fibrillation was significantly larger than that of either controls or group 1 patients. Compared with controls significantly more patients in both groups with atrial fibrillation had consumed alcohol within two days of the onset of the arrhythmia. Significantly more patients had onset of arrhythmia on Wednesday, Thursday, or Friday than on any other weekday, including patients with high alcohol intake. This study establishes alcohol as an important precipitating factor for new onset atrial fibrillation.